2016
DOI: 10.1007/s10964-016-0619-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Anxiety Trajectories from Middle to Late Adolescence

Abstract: Although developmental trajectories of anxiety symptomatology have begun to be explored, most research has focused on total anxiety symptom scores during childhood and early adolescence, using racially/ethnically homogenous samples. Understanding the heterogeneous courses of anxiety disorder symptoms during middle to late adolescence has the potential to clarify developmental risk models of anxiety and to inform prevention programs. Therefore, this study specifically examined gender differences in developmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
61
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 62 publications
9
61
2
1
Order By: Relevance
“…In a 5-year study of Dutch, youth aged between 10 and 12 years at baseline, generalized anxiety disorder, panic disorder, and social anxiety disorder symptoms slightly decreased and then leveled off from early to middle adolescence, followed by a slight increase in generalized anxiety disorder and social anxiety disorder symptoms during middle adolescence and in panic disorder symptoms during late adolescence [22,26]. Similar results have been reported by recent studies [24,27].…”
Section: Prevalencesupporting
confidence: 86%
See 3 more Smart Citations
“…In a 5-year study of Dutch, youth aged between 10 and 12 years at baseline, generalized anxiety disorder, panic disorder, and social anxiety disorder symptoms slightly decreased and then leveled off from early to middle adolescence, followed by a slight increase in generalized anxiety disorder and social anxiety disorder symptoms during middle adolescence and in panic disorder symptoms during late adolescence [22,26]. Similar results have been reported by recent studies [24,27].…”
Section: Prevalencesupporting
confidence: 86%
“…Recent studies showed that, in the general population, anxiety symptoms first decrease during early adolescence and subsequently increase from middle to late adolescence [22]. SAD and SPEC tend to emerge and predominate during childhood, whereas the initial onset of generalized anxiety disorder (GAD), panic disorder (PD), and social anxiety disorder (SAD) most often occurs during adolescence [24,46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we can identify predictors of anxiety disorder trajectories rather than predictors of anxiety onset or anxiety at a singular point in time. Identifying predictors of more persistent, chronic courses of anxiety disorders can help inform prognosis and target intervention efforts to those at a heightened risk for adverse outcomes (Asselmann & Beesdo‐Baum, 2015; Beesdo‐Baum & Knappe, 2012; Ginsburg et al, 2018; Ohannessian, Milan, & Vannucci, 2017).…”
Section: Introductionmentioning
confidence: 99%